Analisis Ketentuan Hak Tanggungan Elektronik pada Peraturan menteri Agraria dan Tata Ruang Nomor 9 Tahun 2019 tentang Pelayanan Hak Tanggungan - Amalia, Nailu Vina; Qurbani, Alifia Soraya; Kumara, Salvian (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
The purpose of this study is to analyze the provisions on Electronic Mortgage. The study uses normative-empirical legal research methods. The approach used is included in the category of Non-Judicial Case Study, which is a legal case study approach without conflict. The data in this study are secondary data obtained from literature sources and existing sources. The analysis used is a descriptive qualitative analysis that describes the actual state of a particular fact. Based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning on Electronic Integrated Mortgage Rights Services, it provides various facilities in its submission. There are several gaps in the regulation that can be used to disadvantage certain parties so that the regulation still needs improvement so that it does not produce a premature product.